Hubungan Karakteristik Ibu Hamil Dengan Tingkat Pengetahuan Tentang Tanda Bahaya Pada Kehamilan Di Puskesmas Galur II - Elina Diassafira; Yunri Merida; Riska Ismawati Hakim (Journal of Midwifery Science: Basic and Applied Research, 2026)
Pregnancy complications remain a leading cause of maternal mortality, yet many can be prevented if danger signs are recognized early. Maternal knowledge is a critical factor in prevention efforts. This study aimed to analyze the relationship between maternal characteristics and knowledge of pregnancy danger signs at Galur II Community Health Center, Kulon Progo. The population consisted of all pregnant women attending antenatal care from January to May 2025 (n = 70). A total of 41 respondents were selected using purposive sampling. A cross-sectional correlational design was applied, and data were collected using a structured questionnaire. Data analysis employed the Fisher Exact test. Results showed significant associations between maternal age (p = 0.005), parity (p < 0.001), educational attainment (p < 0.001), and sources of information (p = 0.008) with knowledge of pregnancy danger signs. In conclusion, maternal age, parity, education level, and access to information were key determinants of knowledge regarding pregnancy danger signs. Strengthening maternal health education and optimizing information sources are recommended to improve awareness and reduce preventable pregnancy complications.